Kinetic variables of the lower limb joint that affect the drop jump index at different drop heights - Yoshida, Takuya; Zushi, Amane; Zushi, Kodayu; Hayashi, Ryohei; Maemura, Hirohiko; Tanigawa, Satoru (Frontiers in Sports and Active Living, 2024)
Background The drop jump index evaluates power exertion in the lower limb stretch-shortening cycle. In addition, the ability to exert power during the stretch-shortening cycle can be evaluated in detail by combining the drop jump index with the kinetic variables of the three lower limb joints. The purpose of this study was to determine the kinetic variables of the three lower limb joints during takeoff that affect the drop jump index of a drop jump from different drop heights. Methods In total, 100 male athletes performed drop jumps from three drop heights (0.3, 0.6, and 0.9 m). Drop jump index and kinetic variables (torque, power, and work) of the three lower limb joints were calculated using body coordinates by infrared camera, and ground reaction force data by force plate. Multiple regression analysis was used to examine the parameters by which the kinetic variables of the three lower limb joints affected the drop jump index. Results As a result, ankle joint and knee joint positive power were extracted as parameters affecting drop jump index at 0.3 m. In addition to these parameters, ankle negative power, ankle negative work and hip eccentric torque at 0.6 m, and knee eccentric torque at 0.9 m were extracted as parameters affecting the drop jump index. Conclusions These results suggest that a higher drop height leads to a greater effect of eccentric torque exertion at the knee and hip joints and of positive power at the ankle and knee joints on the acquisition of the drop jump index.